Antibacterial Activities of Kacapiring Leaf Ethanol Extract (Gardenia jasminoides Ellis) on the Bacteria of Staphylococcus aureus and Propionibacterium acnes - Nuralifah Nuralifah; Fery Indradewi Armadani; Ni Nyoman Fitri Astari (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2019)
ABSTRACTBackground and Objective(s): Infection is the process of entering pathogenic bacteria or microorganisms into the body capable of causing disease. Bacterial infections can cause skin infections such as acne. Acne is inflammation that is accompanied by blockage of the oil glands of the skin and hair (pilosebasea duct). Gardenia jasminoides Ellis is a plant that empirically can be used to treat infectious diseases caused by bacteria. This study was conducted to determine the antibacterial activity of the extracts of kacapiring leaves (Gardenia jasminoides Ellis) against Staphylococcus aureus and Propionibacterium acnes bacteria. Methods: Making extracts was done by maceration method  using  96% ethanol. The concentrations of extracts  used  were 5%, 10% and  15%,  with chloramphenicol and clindamycin as positive controls and distilled water as negative controls. Antibacterial activity was tested by the Cup-plate technique. Results: The antibacterial activity of kacapiring leaves ethanol extract to S. aureus showed that at concentrations of 5%, 10% and 15% the inhibitory power diameters values were respectively 5.58 mm, 9.3 mm and 11.41 mm while the antibacterial activity of extracts kacapiring leaves ethanol to P. acnes bacteria at concentrations of 5%, 10% and 15% had inhibitory power diameters of 6.33 mm, 9.25 mm and 11 mm respectively. Conclusion: Ethanol extract of kacapiring leaves has antibacterial activity against Staphylococcus aureus and Propionibacterium acnes bacteria. At a concentration of 5% and 10%, it shows the moderate category and at a concentration of 15% shows a strong category.Keywords: antibacterial, cup-plate technique , gardenia jasminoides